Biopharmaceutical profiling of anti-infective sanggenons from Morus alba root bark for inhalation administration - Jacqueline Schwarzinger; Sigrid Adelsberger; Karin Ortmayr; Sarah Luise Stellnberger; Ammar Tahir; Gabriela Hädrich; Verena Pichler; Judith M. Rollinger; Ulrike Grienke; Lea Ann Dailey (International Journal of Pharmaceutics: X, 2024)
Mulberry Diels-Alder-type adducts (MDAAs), isolated from Morus alba root bark, exhibit dual activity against viral and bacterial pathogens but show sobering efficacy following oral administration. Inhalation administration may overcome issues with oral bioavailability and improve efficacy for the treatment of respiratory infections. To assess the suitability of MDAAs for inhalation administration, physicochemical (e.g. pH, pKa, logP, pH-dependent solubility) and biopharmaceutical (epithelial cytotoxicity, permeability, and uptake) properties of two bioactive MDAA stereoisomers sanggenon C (SGC) and sanggenon D (SGD) were evaluated as isolated natural compounds and within parent extracts (MA21, MA60). Despite their structural similarity, SGD exhibited a 10-fold higher solubility than SGC across pH 1.2–7.4, with slight increases at neutral pH. Both compounds were more soluble in isolated form than in the parent extracts. The more lipophilic SGC was found to be more cytotoxic when compared to SGD, indicating a better cellular penetration, which was confirmed by uptake studies. Nonetheless, SGC and SGD exhibited no measurable permeability across intact Calu-3 monolayers, highlighting their potential for increased lung retention and improved local anti-infective activity following inhalation administration. Results suggest that SGC and SGD in isolated form, rather than as extracts, are promising candidates for pulmonary drug delivery to treat lung infections.